Hypertension management research priorities from patients, caregivers, and healthcare providers: A report from the Hypertension Canada Priority Setting Partnership Group. Issue 11 (25th September 2017) - Khan, Nadia; Bacon, Simon L.; Khan, Samia; Perlmutter, Sara; Gerlinsky, Carline; Dermer, Mark; Johnson, Lonni; Alves, Finderson; McLean, Donna; Laupacis, Andreas; Pui, Mandy; Berg, Angelique; et al.
Abstract : Patient‐ and stakeholder‐oriented research is vital to improving the relevance of research. The authors aimed to identify the 10 most important research priorities of patients, caregivers, and healthcare providers (family physicians, nurses, nurse practitioners, pharmacists, and dietitians) for hypertension management. Using the James Lind Alliance approach, a national web‐based survey asked patients, caregivers, and care providers to submit their unanswered questions on hypertension management. Questions already answered from randomized controlled trial evidence were removed. A priority setting process of patient, caregiver, and healthcare providers then ranked the final top 10 research priorities in an in‐person meeting. There were 386 respondents who submitted 598 questions after exclusions. Of the respondents, 78% were patients or caregivers, 29% lived in rural areas, 78% were aged 50 to 80 years, and 75% were women. The 598 questions were distilled to 42 unique questions and from this list, the top 10 research questions prioritized included determining the combinations of healthy lifestyle modifications to reduce the need for antihypertensive medications, stress management interventions, evaluating treatment strategies based on out‐of‐office blood pressure compared with conventional (office) blood pressure, education tools and technologies to improve patient motivation and health behavior change, management strategies for ethnic groups, evaluating natural and alternative treatments, and the optimal role of different healthcare providers and caregivers in supporting patients with hypertension. These priorities can be used to guide clinicians, researchers, and funding bodies on areas that are a high priority for hypertension management research for patients, caregivers, and healthcare providers. This also highlights priority areas for improved knowledge translation and delivering patient‐centered care.